Factors Associated with Exclusive Breastfeeding in Timor-Leste: Findings from Demographic and Health Survey 2009-2010 - Khanal, Vishnu; da Cruz, J.; Karkee, R.; Lee, Andy (MDPI Publishing, 2014)
Exclusive breastfeeding is known to have nutritional and health benefits. This study investigated factors associated with exclusive breastfeeding among infants aged five months or less in Timor-Leste.The latest data from the national Demographic and Health Survey 2009-2010 were analyzed by binary logistic regression. Of the 975 infants included in the study, overall 49% (95% confidence interval 45.5% to 52.7%) were exclusively breastfed. The exclusive breastfeeding prevalence declined with increasing infant age, mothers with a paid occupation, who perceived their newborn as non-average size, and residence in the capital city Dili, was associated with a lower likelihood of exclusive breastfeeding. On the other hand, women who could decide health-related matters tended to breastfeed exclusively, which was not the case for others whose decisions were made by someone else. The results suggested the need of breastfeeding promotion programs to improve the exclusive breastfeeding rate. Antenatal counseling, peer support network, and home visits by health workers could be feasible options to promote exclusive breastfeeding given that the majority of births occur at home.